2011
DOI: 10.1002/anie.201100514
|View full text |Cite
|
Sign up to set email alerts
|

An Efficient Approach to the Synthesis of Nucleosides: Gold(I)‐Catalyzed N‐Glycosylation of Pyrimidines and Purines with Glycosyl ortho‐Alkynyl Benzoates

Abstract: Persuaded with gold: The title reaction in the presence of [Ph3PAuNTf2] (Tf=trifluoromethanesulfonyl) led conveniently to the corresponding nucleosides with excellent regioselectivity (see scheme). Even purine derivatives underwent this transformation owing to the mild conditions, which enabled the use of protecting groups that would not usually be compatible with N‐glycosylation conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
73
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 156 publications
(81 citation statements)
references
References 60 publications
5
73
0
Order By: Relevance
“…13 Hotha and co-workers also found that using thiols as aglycones and AuBr 3 as a catalyst, propargyl glycosides 33 could be converted into thioglycosides, which are an important kind of glycosyl donors for glycochemists (Scheme 7). Propargyl mannoside offered a-thioglycosides with 1,2-trans stereoselectivity (34), while propargyl glucoside and galactoside resulted in a mixture of a,b-thioglycosides (35,36). This procedure could also be applied to the synthesis of thiodisaccharide 37 from corresponding disaccharide propargyl glycoside.…”
Section: Gold(iii)-catalyzed Glycosidation With Propargyl Glycoside Dmentioning
confidence: 92%
See 1 more Smart Citation
“…13 Hotha and co-workers also found that using thiols as aglycones and AuBr 3 as a catalyst, propargyl glycosides 33 could be converted into thioglycosides, which are an important kind of glycosyl donors for glycochemists (Scheme 7). Propargyl mannoside offered a-thioglycosides with 1,2-trans stereoselectivity (34), while propargyl glucoside and galactoside resulted in a mixture of a,b-thioglycosides (35,36). This procedure could also be applied to the synthesis of thiodisaccharide 37 from corresponding disaccharide propargyl glycoside.…”
Section: Gold(iii)-catalyzed Glycosidation With Propargyl Glycoside Dmentioning
confidence: 92%
“…35 Using glycosyl (ribofuranosyl, arabinofuranosyl, glucopyranosyl, and rhamnopyranosyl) ortho-hexynylbenzoates 94 as donors, N-Boc protected . 36 During the systematic investigation of Au(I)-catalyzed glycosylation by use of glycosyl ortho-alkynylbenzoates as donors, some serendipitous outcomes were obtained and exploited by Yu and co-workers. One was the discovery of a dramatic concentration effect on the Scheme 18 Scheme 19 stereoselectivity of N-glycosylation.…”
Section: Gold(i)-catalyzed Glycosylation With Glycosyl Ortho-alkynylbmentioning
confidence: 98%
“…97 The method is amenable to N -glycosylation strategies, which was demonstrated with the synthesis of purine and pyrimidine nucleobases. 98 In this review, we will showcase the utility of Au(I)-catalyzed glycosylation with ortho -hexynylbenzoate donors in the synthesis of TMG-chitotriomycin, lupane-type saponins, and glycopolymers.…”
Section: Glycosyl Trichloroacetimidate Ortho-alkynyl-benzoate Anmentioning
confidence: 99%
“…NBBAs were water soluble and purified through reversed‐phase column chromatography (SiliCycle, SiliaSphere C18) to remove the monoquaternized minor products. Finally, NBBAs were deprotected by refluxing in the mixed solvents of t BuOH and H 2 O to afford the desired NHBAs (NH o BA, NH m BA, NH p BA) quantitatively.…”
Section: Methodsmentioning
confidence: 99%
“…The secondary amine 1 was protected by tert-butoxycarbonyl (Boc) group to afford compound 2.T hen, the N-Boc protected diboronic acids (NBBAs, including NBoBA, NBmBA, NBpBA)w ere obtained through the reactions of 2 with excess boronic acid-appended benzylb romides.N BBAs werew ater soluble and purified through reversed-phase column chromatography (SiliCycle, SiliaSphere C18) to remove the monoquaternized minor products. Finally, NBBAs were deprotected by refluxing in the mixed solvents of tBuOH andH 2 O [14] to afford the desired NHBAs (NHoBA, NHmBA,N H pBA) quantitatively.…”
mentioning
confidence: 99%